Pelatihan Pencegahan Penularan Penyakit Scabies dan Peningkatan Hidup Bersih dan Sehat Bagi Santriwan - Lensoni; Yulinar; Meliyana; Cut Rahmawati; Erna Safitri; Dini Rahmayani (Universitas Lancang Kuning, 2020)
Scabies is a highly contagious skin disease in humans and other mammals caused by the parasitic mite sarcoptes scabiei. The main transmission of scabies is from direct physical contact, so scabies is susceptible to spread in a closed environment that is densely populated, such as houses, dormitories, and boarding schools. The location of the training is at Sulaimania Boarding School in Kuta Baro District, Aceh Besar Regency. The objective to be achieved from the training activities is to increase the knowledge of students at Sulaimania Islamic Boarding School, through the dissemination of knowledge about clean and healthy living behaviors to prevent scabies. The method used in the form of lectures, practice and frequently asked questions. Evaluation of training activities is carried out by distributing questionnaires before and after the activity. The evaluation showed that overall there was an increase approximately 60.34% in students' understanding of the prevention of scabies and healthy and clean living behaviors and the participants benefited from this training.